Комплексная демагнетизация труб при электродуговой сварке - Волохов, С.А.; Добродеев, П.Н.; Мамин, Г.И. (Технічна електродинаміка, 2012)
The selectivity and efficacy of methods of demagnetization of joined for welding magnetized large-diameter pipes are investigated. It is determined that integrated demagnetization of pipes during repair works on main pipelines, which represents the sequential use of methods of degaussing and compensation, allows to reliably reduce the magnetic field in the weld area to the level which does not adversely affect the welding process.